Macroeconomic Determinants of Consumer Lending in Saudi Arabia - Alnefaee, Saad M. (Journal of Accounting, Business and Finance Research, 2019)
This paper empirically investigates the macroeconomic variables that influence consumer lending in Saudi Arabia using quarterly data for the period of 1996-2017. The Johansen and Juselius (1990) multivariate cointegration test were used to examine the impact of banks liquidity, interest rate, oil prices and GDP per capita on consumer lending. The test results indicate the existence of the long-term relationship and the empirical results show that consumer lending is positively influenced by a change in banks liquidity, growth in oil prices and GDP per capita. Contrary to expectation, the interest rate was positive and significant. The modified Granger causality test in Error Correction Model framework reports bidirectional causality from banks liquidity to consumer lending and vice versa, while unidirectional causality from GDP per capita and interest rate to consumer lending. The main finding of the paper is to encourage the monetary authority to allow for a gradual phase-out of restrictions on the number of personal loans as well as enhancing consumer protection mechanism to prohibit unfair contractual terms in the agreements.